Peran Pendidikan Agama Islam Dalam Pembentukan Etika Sosial Peserta Didik Perspektif Tafsir Al-Bayan - Tri Wahyuni; Enjang Burhanudin Yusuf (CV. ITTC INDONESIA, 2025)
Background: The modern era presents serious challenges to the formation of students’ character and social ethics. The degradation of moral values such as individualism, materialism, and the weakening of social solidarity requires Islamic religious education to play a more strategic role in building the ethical awareness of the younger generation. Research Objectives: This study aims to: (1) analyze the concept of social ethics from the perspective of Tafsir Al-Bayan by Imam Abdul Hamid Hakim, (2) identify the role of Islamic education in shaping students’ social ethics, and (3) formulate pedagogical implications for the development of a social-ethics-based Islamic Education (PAI) curriculum.Methods: This research employs a qualitative approach using library research methods. Primary data were obtained from Tafsir Al-Bayan, while secondary data were sourced from Islamic education literature, academic journals, and books related to social ethics. Data were analyzed using content analysis techniques with a hermeneutic approach to understand the textual and contextual meanings of Qur’anic verses related to social ethics.Main Findings: The results show that Tafsir Al-Bayan emphasizes three dimensions of social ethics: (1) ta'awun (mutual assistance) as the foundation of social solidarity, (2) ihsan (benevolence) as the orientation of interpersonal behavior, and (3) ‘adl (justice) as the principle of distributing rights and responsibilities. Islamic education serves as a medium for internalizing these values through integrative learning that connects sacred texts with contemporary social realities. Implications: These findings contribute to the development of PAI learning models that are not only oriented toward ritual-worship aspects but also toward the formation of students’ ethical and social awareness. PAI teachers need to integrate contextual tafsir approaches into the learning process to bridge Qur’anic values with present-daysocialissues.